2021
DOI: 10.20884/1.jap.2021.23.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Estrous Performance of Etawah Crossbred Goats Following Different Estrous Synchronization Methods

Abstract: The objective of the research was to determine the estrous profile of Etawah Crossbred goats after estrous synchronization with different methods. Eighteen does aged 12-24 month old were divided in three groups to receive estrous synchronization treatments (T1 = 14 days intravaginal implant of 60 mg of progesterone  (MPA), T2 = two times injection of 5 mg PGF2α (lutalyse) in 11 days interval, and T3 = 10 days of intravaginal implant of 60 mg of progesterone  (MPA) + injection of 5 mg PGF2α 48 hours before remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
1
0
2
Order By: Relevance
“…The use of intravaginal implants in combination with eCG in the schemes of synchronization-stimulation of sexual desire in transgenic females allows to effectively and in the shortest possible time to carry out work on inducing oestrus in goats, shorten the duration of sexual heat in animals and contributes to a more synchronous manifestation of oestrus in the anoestrous period of animal reproduction (Kirikovich et al, 2019). Solihati et al (2021) determined the oestrous profile of Etawah Crossbred goats after oestrous synchronization by different methods: Type 1 (T1) -14 days of intravaginal implant 60 mg progesterone (MPA); Type 2 (T2) -two injections of 5 mg PGF2α (dinoprost tromethamine; Lutalyse) 11 days apart; Type 3 (T3) -10 days of intravaginal implantation of 60 mg of progesterone (MPA) + injection of 5 mg of PGF2α 48 hours before removal). The results showed that oestrus behaviour and changes in colour and size of the vulva did not differ significantly in contrast to the duration of oestrus.…”
Section: Discussionmentioning
confidence: 99%
“…The use of intravaginal implants in combination with eCG in the schemes of synchronization-stimulation of sexual desire in transgenic females allows to effectively and in the shortest possible time to carry out work on inducing oestrus in goats, shorten the duration of sexual heat in animals and contributes to a more synchronous manifestation of oestrus in the anoestrous period of animal reproduction (Kirikovich et al, 2019). Solihati et al (2021) determined the oestrous profile of Etawah Crossbred goats after oestrous synchronization by different methods: Type 1 (T1) -14 days of intravaginal implant 60 mg progesterone (MPA); Type 2 (T2) -two injections of 5 mg PGF2α (dinoprost tromethamine; Lutalyse) 11 days apart; Type 3 (T3) -10 days of intravaginal implantation of 60 mg of progesterone (MPA) + injection of 5 mg of PGF2α 48 hours before removal). The results showed that oestrus behaviour and changes in colour and size of the vulva did not differ significantly in contrast to the duration of oestrus.…”
Section: Discussionmentioning
confidence: 99%
“…Pada sisi lain, kondisi seperti ini sangat jarang ditemukan di tingkat lapangan karena siklus estrus antar individu ternak sangat bervariasi. (Solihati et al, 2021a;Setiawan et al, 2017) ataupun dengan penggunaan CIDR pada kambing PE (Solihati et al, 2021b), kambing Boer (Anwar et al, 2020, kambing Kacang dan kambing Bligon (Popalayah et al, 2014). Sinkronisasi estrus dengan progesterone intravaginal juga mampu meningkatkan efisiensi reproduksi kambing PE pasca beranak (Supriyanto, 2014), demikian pula pada domba, pemberian CIDR, PMSG, dan genistein dapat meningkatkan karakteristik estrus (Mangun et al, 2022).…”
Section: Pendahuluanunclassified
“…Ketepatan deteksi berahi dapat dibantu dengan penerapan metode sinkronisasi berahi atau sinkronisasi estrus. Penelitian mengenai metode sinkronisasi estrus pada ternak kecil seperti domba dan kambing sudah dilakukan oleh beberapa peneliti diantaranya dengan menggunakan spons vaginal pada kambing Peranakan Etawah (PE) (Solihati et al, 2021a;Setiawan et al, 2017) dengan harga yang ekonomis terjangkau oleh peternak kecil, penggunaan implan CIDR pada kambing PE (Solihati et al, 2021b) dan CIDR pada Kambing Boer (Anwar et al, 2020) Inseminasi Buatan (IB) diartikan sebagai proses memasukkan semen/mani yang berasal dari kelamin jantan ke dalam kelamin betina dengan bantuan manusia. Dalam pengertian lebih jauh IB adalah bagian dari artificial breeding atau pemuliabiakan dengan campur tangan keahlian manusia untuk menghasilkan secara intensif turunan ternak yang bermutu.…”
Section: Pendahuluanunclassified